2009
DOI: 10.1051/alr/2009010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation for carcass quality traits in cultured sea bass (Dicentrarchus labrax)

Abstract: -Genetic parameters for carcass quality traits were estimated in 27 families of sea bass (3 dams × 9 sires factorial mating design), raised mixed in the same tanks starting before hatching. Offspring parentage was determined a posteriori using 6 microsatellite loci. Carcass quality traits were recorded at 818 days post fertilization (mean standard length: 32.6 ± 3.1 cm). Genetic parameters were estimated from the sire half sib variance and covariance components. Heritability of body weight (BW) and carcass pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
33
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 33 publications
5
33
5
1
Order By: Relevance
“…marker assisted selection. From such communally bred families, quantitative genetic parameters have been reported for heritabilities and phenotypic and genotypic correlations for some traits, such as sex (Vandeputte et al 2007), body weight and length (Vandeputte & Launey 2004;Saillant et al 2006;Chatziplis et al 2007) and carcass traits (Saillant et al 2009). From such communally bred families, quantitative genetic parameters have been reported for heritabilities and phenotypic and genotypic correlations for some traits, such as sex (Vandeputte et al 2007), body weight and length (Vandeputte & Launey 2004;Saillant et al 2006;Chatziplis et al 2007) and carcass traits (Saillant et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…marker assisted selection. From such communally bred families, quantitative genetic parameters have been reported for heritabilities and phenotypic and genotypic correlations for some traits, such as sex (Vandeputte et al 2007), body weight and length (Vandeputte & Launey 2004;Saillant et al 2006;Chatziplis et al 2007) and carcass traits (Saillant et al 2009). From such communally bred families, quantitative genetic parameters have been reported for heritabilities and phenotypic and genotypic correlations for some traits, such as sex (Vandeputte et al 2007), body weight and length (Vandeputte & Launey 2004;Saillant et al 2006;Chatziplis et al 2007) and carcass traits (Saillant et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Large scale profiling of paternity with microsatellite markers has facilitated the breeding of families on an experimental and commercial scale in a reliable and affordable fashion (García de Léon et al 1995;Chatziplis et al 2007). From such communally bred families, quantitative genetic parameters have been reported for heritabilities and phenotypic and genotypic correlations for some traits, such as sex (Vandeputte et al 2007), body weight and length (Vandeputte & Launey 2004;Saillant et al 2006;Chatziplis et al 2007) and carcass traits (Saillant et al 2009). Heritabilities for growth are relatively high and vary from 0.29 to 0.60 in European sea bass (Saillant et al 2006;Dupont-Nivet et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Known as a valuable trait in this species, fat deposition is known to be affected by dietary carbohydrate levels as well as protein sources (Dias et al 2005). Saillant, Dupont‐Nivet, Sabourault, Haffray, Laureau, Vidal and Chatain (2009) demonstrated that the quality of prediction of lipid content with Distell Fish Fatmeter, previously used on rainbow trout (Douirin, Haffray, Vallet & Fauconneau 1998; Quillet, Le Guillou, Aubin & Fauconneau 2005; Quillet, Le Guillou, Aubin, Labbé, Fauconneau & Médale 2007), was accurate enough to assess genetic parameters in sea bass, with a moderate heritability (0.28 ± 0.12) for this trait. We measured and followed this trait during our trial.…”
Section: Introductionmentioning
confidence: 99%
“…The fatmeter measures the water content of the tissues beneath the skin, which relates to the amount of lipid stored in subdermal reserves and associated peripheral muscle tissues (hereafter, subdermal lipids). For many species, measures of subdermal lipid content from the fatmeter are well correlated with wholefish or fillet lipid content measured by proximate composition analysis (0.58 ≤ r 2 ≤ 0.87; Vogt et al 2002;Hendry and Beall 2004;Bransden et al 2007;Kaga et al 2009;Saillant et al 2009;Van Sang et al 2009;Caldwell et al 2013;Mesa and Rose 2015), but these relationships have often been developed for adult fish only, and the species investigated thus far are those that are likely to accumulate large lipid stores as adults.…”
mentioning
confidence: 99%